Inflammatory characteristics of adipose tissue collected by surgical excision vs needle aspiration - Santosa, S; Swain, J; Tchkonia, T; Kirkland, J L; Jensen, M D (International Journal of Obesity, 2015)
Subcutaneous adipose tissue can be obtained for research during an elective, clinically indicated operation by standard surgical excision approaches and by needle aspiration in pure research settings. Whether measurements of inflammatory markers and cells from tissues collected in these two different ways are comparable is debatable. We sought to determine whether these two techniques yield systematically different results for measurements of inflammation, cellular senescence and adipose tissue composition. Twelve subjects undergoing surgery participated. At the time of surgery abdominal subcutaneous adipose tissue from adjacent sites was removed by excision and needle aspiration. Stromovascular cell composition (flow cytometry), the number of senescent cells (senescence-associated-β-galactosidase staining) and interleukin (IL)-6, IL-1, TNF-α and MCP1 mRNA (reverse transcription-PCR) were measured in each sample. We found no statistically significant differences between the two sample-collection approaches for any of the parameters measured. We conclude that these two methods of obtaining adipose tissue do not systematically differ in the results of cytokine mRNA content, cellular senescence or stromovascular cell composition.